Use Of Edmodo As A Virtual Class Learning Model In Smk Bakti Utama Merbau Mataram Regency Of Southern Lampung - Eka Ridhawati; Ahmad Khumadi; Ponidi - (Prosiding International conference on Information Technology and Business (ICITB), 2017)
The background of this research is to develop learning through internet media, which aims to build online class based virtual by using Edmodo application, as supporting medium of learning processess. This research uses Rapid Application Development (RAD), which is used to develop an educational product. This method has a good level of validation because it is done through the stages of field trials and known level of effectiveness. Stages in the application of RAD is Business Modeling, Data Modeling, Process Modeling, Aplication Generation, and Testing and Turnover. The results show that building an online class based online by using Edmodo application can improve the motivation and quality of student learning. Based on the pooling results obtained 70% stated Agree, 20% stated Strongly Agree, 10% stated Disagree and 0% Strongly Disagree. Keywords : Virtual Class, EDMODO, and Based Online.